Pengaruh Harga Tiket Pesawat Terhadap Kunjungan Wisatawan ke Provinsi Kepulauan Bangka Belitung - tarji, muahamad (Jurnal Penelitian Ilmu Pariwisata, 2025)
This study analyzes the impact of airplane ticket prices on tourist visits to the Bangka Belitung Islands Province using secondary statistical data from official online sources, such as the Central Statistics Agency (BPS), the Tourism Office, and national online media. The results indicate that high airplane ticket prices are a key factor in the decline of tourist visits, particularly post-COVID-19 pandemic. The reduction in flight frequency and the high cost of tickets compared to other destinations have led tourists to choose more affordable alternatives. This study recommends policy adjustments to lower ticket prices and increase flight frequency to enhance the competitiveness of tourism in Bangka Belitung.